The Influence of Islamic Leadership Style and Islamic Work Ethics on Employee Performance at the BMT Trans Redjo Mulyo Dadi Office, Muara Telang District - Ahmad Fahrurozi, Hilda, Fakhrina (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2024)
Employee Performance refers to the ability of employees to carry out all the tasks for which they are responsible. This study aims to analyze the influence of independent variables, namely Islamic Leadership Style and Islamic Work Ethics on the dependent variable, namely Employee Performance. This study used a sample, namely BMT Trans Redjo Mulyo Dadi Employees, Muara Telang District. This research was carried out by a data collection method in the form of a questionnaire distributed to 30 BMT Trans Redjo Mulyo Dadi Employees, Muara Telang District. Then a quantitative analysis of the data obtained was carried out. The quantitative analysis includes testing data instruments, descriptive statistics, classical assumption tests (normality test, linearity test, multicollineitary test and heterokedasticity test), multiple regression analysis and hypothesis test (determination coefficient (Adjusted R Square), F test and T test). The results of this study show that Islamic Leadership Style partially has a significant positive effect on Employee Performance. Then Islamic Work Ethics partially has a significant positive influence on Employee Performance. And simultaneously Islamic Leadership Style and Islamic Work Ethics have a significant effect on Employee Performance. The Adjusted R Square figure is 0.738 which means that 73.8% of Employee Performance can be explained by the two independent variables in the study, while 26.2% is explained by factors outside the study.